FgLEU1 Is Involved in Leucine Biosynthesis, Sexual Reproduction, and Full Virulence in Fusarium graminearum - Shaohua Sun; Mingyu Wang; Chunjie Liu; Yilin Tao; Tian Wang; Yuancun Liang; Li Zhang; Jinfeng Yu (Journal of Fungi, 2022)
Fusarium head blight (FHB) caused by Fusarium graminearum is a significant disease among cereal crops. In F. graminearum, biosynthesis of leucine, which is a branched chain amino acid, is achieved by converting α-isopropylmalate to β-isopropylmalate catalyzed by isopropylmalate isomerase encoded by LEU1. Considering the potential for targeting this pathway by fungicides, we characterized the gene FgLEU1 (FGSG-09589) in the Fusarium graminearum genome using bioinformatics methods. For functional characterization, we constructed a deletion mutant of FgLEU1 (ΔLEU1) through homologous recombination. Compared with the wild-type strain PH-1, ΔLEU1 showed slower colony growth and fewer aerial mycelia. Leucine addition was needed to ensure proper mutant growth. Further, ΔLEU1 showed decreased conidial production and germination rates, and could not produce ascospores. Moreover, ΔLEU1 showed complete loss of pathogenicity and reduced ability to produce deoxynivalenol (DON) and aurofusarin. Upstream and downstream genes of FgLEU1 were significantly upregulated in ΔLEU1. Contrary to previous reports, the deletion mutant was more resistant to osmotic stress and cell wall-damaging agents than the wild-type. Taken together, FgLEU1 plays a crucial role in leucine synthesis, aerial mycelial growth, sexual and asexual reproduction, pathogenicity, virulence, and pigmentation in Fusarium graminearum, indicating its potential as a target for novel antifungal agents.